2007
DOI: 10.1098/rstb.2007.0011
|View full text |Cite
|
Sign up to set email alerts
|

Early growth conditions, phenotypic development and environmental change

Abstract: Phenotypic development is the result of a complex interplay involving the organism's own genetic make-up and the environment it experiences during development. The latter encompasses not just the current environment, but also indirect, and sometimes lagged, components that result from environmental effects on its parents that are transmitted to their developing offspring in various ways and at various stages. These environmental effects can simply constrain development, for example, where poor maternal conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
970
10
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 853 publications
(1,021 citation statements)
references
References 66 publications
39
970
10
2
Order By: Relevance
“…Gluckman and Hanson 2004;Lindström 1999;Lummaa and CluttonBrock 2002;Metcalfe and Monaghan 2001). Long-term consequences of early developmental conditions have, however, been found to vary with the quality of the adult environment in opposing ways (reviewed in Monaghan 2008). First, it has been demonstrated that nestlings raised under poor conditions suffer a suboptimal development and experience negative effects irrespective of the quality of the adult environment (Grafen 1988;Monaghan 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gluckman and Hanson 2004;Lindström 1999;Lummaa and CluttonBrock 2002;Metcalfe and Monaghan 2001). Long-term consequences of early developmental conditions have, however, been found to vary with the quality of the adult environment in opposing ways (reviewed in Monaghan 2008). First, it has been demonstrated that nestlings raised under poor conditions suffer a suboptimal development and experience negative effects irrespective of the quality of the adult environment (Grafen 1988;Monaghan 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term consequences of early developmental conditions have, however, been found to vary with the quality of the adult environment in opposing ways (reviewed in Monaghan 2008). First, it has been demonstrated that nestlings raised under poor conditions suffer a suboptimal development and experience negative effects irrespective of the quality of the adult environment (Grafen 1988;Monaghan 2008). Second, several studies found that long-term effects of developmental stress remain masked under favourable adult conditions as physiological responses are not affected by an individual's quality (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, several studies of mammals and birds have shown that parents cannot fully compensate for the increased energetic requirement of an enlarged brood (Monaghan, 2008; Rémy et al., 2011). Bonelli’s eagles usually lay one or two eggs (Real, 1991), so females have to face a trade‐off between forming one or two eggs at the time of egg formation.…”
Section: Discussionmentioning
confidence: 99%
“…We considered past productivity, the number of chicks in each nest, and their interactions as explanatory variables. The number of reared chicks was included because it has been shown to have an effect on the body condition of nestlings in several long‐lived bird species (Monaghan, 2008). …”
Section: Methodsmentioning
confidence: 99%